Diagnosis and Therapy Before Assisted Reproductive Treatments. Guideline of the DGGG, OEGGG and SGGG (S2k Level, AWMF Register Number 015-085, February 2019) – Part 1, Basic Assessment of the Woman - Toth, Bettina; Baston-Büst, Dunja Maria; Behre, Hermann M; Bielfeld, Alexandra; Bohlmann, Michael; Bühling, Kai; Dittrich, Ralf; Goeckenjan, Maren; Hancke, Katharina; Kliesch, Sabine; Köhn, Frank-Michael; Krüssel, Jan; Kuon, Ruben; Liebenthron, Jana; Nawroth, Frank; Nordhoff, Verena; Pinggera, Germar-Michael; Rogenhofer, Nina; Rudnik-Schöneborn, Sabine; Schuppe, Hans-Christian; Schüring, Andreas; Seifert-Klauss, Vanadin; Strowitzki, Thomas; Tüttelmann, Frank; Vomstein, Kilian; Wildt, Ludwig; Wischmann, Tewes; Wunder, Dorothea; Zschocke, Johannes (Geburtshilfe und Frauenheilkunde, 2019)
Introduction Supporting and counselling couples with fertility issues prior to starting ART is a multidisciplinary diagnostic and therapeutic challenge. The first German/Austrian/Swiss interdisciplinary S2k guideline on “Diagnosis and Therapy Before Assisted Reproductive Treatments (ART)” was published in February 2019. This guideline was developed in the context of the guidelines program of the German Society of Gynecology and Obstetrics (DGGG) in cooperation with the Swiss Society of Gynecology and Obstetrics (SGGG) and the Austrian Society of Gynecology and Obstetrics (OEGGG).Aims One third of the causes of involuntary childlessness are still unclear, even if the woman or man have numerous possible risk factors. Because the topic is still very much taboo, couples may be socially isolated and often only present quite late to a fertility center. At present, there is no standard treatment concept, as currently no standard multidisciplinary procedures exist for the diagnostic workup and treatment of infertility. The aim of this guideline is to provide physicians with evidence-based recommendations for counselling, diagnostic workup and treatment.Methods This S2k guideline was developed on behalf of the Guidelines Commission of the DGGG by representative members from different professional medical organizations and societies using a structured consensus process.Recommendations The first part of this guideline focuses on the basic assessment of affected women, including standard anatomical and endocrinological diagnostic procedures and examinations into any potential infections. Other areas addressed in this guideline are the immunological workup with an evaluation of the patientʼs vaccination status, an evaluation of psychological factors, and the collection of data relating to other relevant factors affecting infertility. The second part will focus on explanations of diagnostic procedures compiled in collaboration with specialists from other medical specialties such as andrologists, human geneticists and oncologists.Einleitung Die Begleitung von Paaren mit unerfülltem Kinderwunsch vor einer ART ist eine multidisziplinäre diagnostische und therapeutische Herausforderung. Im Februar 2019 erschien die erste deutschsprachige interdisziplinäre S2k-Leitlinie für die „Diagnostik und Therapie vor einer assistierten reproduktionsmedizinischen Behandlung (ART)“. Die Leitlinienerstellung erfolgte im Rahmen des Leitlinienprogrammes der Deutschen Gesellschaft für Gynäkologie und Geburtshilfe (DGGG) in Kooperation mit der Schweizer Gesellschaft für Gynäkologie und Geburtshilfe (SGGG) und der Österreichischen Gesellschaft für Gynäkologie und Geburtshilfe (OEGGG).Ziel Ein Drittel der Ursachen für Kinderlosigkeit bleibt unklar, auch wenn es eine Vielzahl an möglichen Risikofaktoren aufseiten der Frau und des Mannes gibt. Aufgrund der immer noch vorhandenen Tabuisierung des Themas sind die Paare teilweise sozial isoliert und wenden sich oftmals erst spät an ein Kinderwunschzentrum. Derzeit besteht kein einheitliches Behandlungskonzept, da keine fächerübergreifenden Handlungsanweisungen zur Diagnostik und Therapie der Infertilität vorliegen. Ziel der Leitlinie ist es, dem behandelnden Arzt/Ärztin im Rahmen der Beratung, diagnostischen Abklärung und Behandlung evidenzbasierte Empfehlungen anzubieten.Methoden Diese S2k-Leitlinie wurde durch einen strukturierten Konsens von repräsentativen Mitgliedern verschiedener Fachgesellschaften im Auftrag der Leitlinienkommission der DGGG entwickelt.Empfehlungen In diesem 1. Teil wird die grundlegende Abklärung der Frau thematisiert, mitsamt der grundlegenden anatomischen, endokrinologischen und infektiologischen Diagnostik. Darüber hinaus werden die immunologische Diagnostik, wie etwa die Abklärung des Impfstatus, die Evaluation psychologischer Faktoren sowie die Erhebung weiterer relevanter Einflussfaktoren auf die Infertilität thematisiert. Im 2. Teil erfolgt die Erläuterung der Abklärung in Zusammenarbeit mit anderen Fachdisziplinen wie Andrologen, Humangenetikern und Onkologen.
Keywords: infertility; preconception counselling; endometriosis; PCOS; guideline